PENGARUH CITRA MEREK TERHADAP GAYA KEPUTUSAN KONSUMEN PADA PRODUK STARBUCKS - Firda Ridhania (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract The aim of this research is for analyzing a influence brand image with consumer decision-making styles . The sample in this research amount 85 persons. The Sampling is using a non probability sampling technique, purposive sampling. Assessment tools in the form of questionnaires, which consist of Likert-Scale. The Process of data sampling is using two scales; those are Brand Image Scale and Consumer Decision-Making Styles Scale. Brand Image Scale was adopted from journals The Effect Of Brand Image On Overall Satisfaction And Loyalty Intention In The and - . For measuring consumer decision-making styles is using Consumer Style Inventory (CSI) that was developed by Kendall and Sproles (1986). Data Analysis in this research is using simple regression analysis with the result of correlation coefficient at number 0,498(r = 0,498 p<0,05) and the result regression of Y = 31,634 + 0,233X. The analysis result in this Research is Brand Image as an Independent Variable has a significant impact on the dependent variable and the consumer decision-making styles. Keywords: Brand Image, Consumer Decision-Making Styles, Starbucks